PENGARUH PUPUK KOMPOS DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS BIMA - Osfinetri, Osfinetri; Tadjudin, Endang; Sungkawa , Iman (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This study aimed to investigate the effects of compost and NPK fertilizers on the growth and yield of shallot plants (Allium ascalonicum L., Bima variety), to determine the optimal rates of compost and NPK for achieving high yields, and to examine the correlations between yield components and total yield. The experiment was carried out from June to August 2022 at the Agricultural Complex, Ma’had Al-Zaytun Campus, Indramayu, West Java, located at an altitude of approximately 50 meters above sea level. The soil at the site was classified as latosol with a pH of 5.5 and a clay texture (80.16%). The area has a Type C climate, characterized by moderately wet conditions, monthly rainfall ranging from 4 to 63.4 mm, and an average temperature of 32°C. The research used an experimental approach with a Randomized Complete Block Design (RCBD) in a factorial arrangement of nine treatment combinations of compost and NPK fertilizers. Compost was applied at three levels (1.5, 2, and 2.5 t/ha), while NPK was applied at three levels (150, 200, and 250 kg/ha). Each treatment was replicated three times, resulting in 27 plots, each measuring 3 m². The collected data were analyzed using analysis of variance (ANOVA) and Scott-Knott’s multiple comparison test, while correlations between growth components and yield were assessed using the Pearson Product Moment correlation. The highest dry bulb yield was obtained from the combination E (2 t/ha compost + 200 kg/ha NPK), producing 3.92 kg/plot, equivalent to 9.8 t/ha. Significant relationships were observed for root volume, plant growth rate, number of tillers, bulb diameter, fresh bulb weight per plant, fresh bulb weight per plot, dry bulb weight per plant, and dry bulb weight per plot, with a strong correlation between the number of tillers, number of bulbs, and dry bulb weight per plot.